Does Abnormal Preoperative Coagulation Status Lead to More Perioperative Blood Loss in Spinal Deformity Correction Surgery? - Li, Zheng; Yu, Bin; Zhang, Jianguo; Shen, Jianxiong; Wang, Yipeng; Qiu, Guixing; Cheng, Xinqi (Frontiers in Surgery, 2022)
This study aims to analyze the potential association between the preoperative coagulation status and perioperative blood loss in spinal deformity correction surgery. The preoperative coagulation status and estimated blood loss (EBL) during operation, postoperative wound drainage, and allogeneic transfusion during and after operation were recorded and analyzed. Among the 164 patients, 26 had a longer prothrombin time (PT), 13 had a lower fibrinogen level, 55 had a longer activated partial thromboplastin time (APTT), and 2 had a longer thrombin time (TT), and the platelet count (PLT) was all normal or higher than the normal level. The mean EBL per surgical level was 77.8 ml (range, 22–267 ml), and the mean drainage per surgical level was 52.7 ml (range, 7–168 ml). Fifty-five patients and 12 patients underwent allogeneic transfusion during and after the operation, respectively. The differences in EBL per surgical level, mean drainage per surgical level, the occurrences of allogeneic transfusion during and after operation between the patients with a longer PT, lower fibrinogen level, longer APTT or longer TT, and the normal controls were not significant (all P’s > 0.05). The Spearman correlation analysis showed that there was no correlation between PT, fibrinogen, APTT, TT or PLT with EBL per surgical level, mean drainage per surgical level, or allogeneic transfusion during and after the operation (all P’s > 0.05). The abnormal preoperative coagulation status but not hemophilia does not lead to more perioperative blood loss or a higher rate of perioperative allogeneic transfusion in spinal deformity correction surgery.